15. Aspects of Musical Language of Heitor Villa-Lobos' Concert Studies - Dragomirescu Daniel (Sciendo, 2021)
Careful research has shown that the Brazilian composer's works are inaccurate in terms of indications yet respecting every parameter of music. Regarding the technical aspects, which represent the quintessence in the interpretation of string instruments, and in our case, a dark realm due to the lack of their representation on the score, the performer must make balanced decisions based on imagination and education acquired during years of study.